Bi-directional longitudinal associations between different types of bullying victimization, suicide ideation/attempts, and depression among a large sample of European adolescents - Brunstein-Klomek, Anat; Brunner, Romuald; Kaess, Michael (The journal of child psychology and psychiatry, 2019)
Background The association between bullying victimization and depression, suicide ideation and suicide attempts has been studied mainly in cross-sectional studies. This study aims to test the bidirectional effect and the chronicity versus sporadic effect of physical, verbal, and relational bullying victimization on suicidal ideation/attempts and depression. Methods Longitudinal assessments with an interval of 3- and 12-months were performed within a sample of 2,933 adolescents (56.1% females; mean age 14.78, SD = .89) from 10 European countries, participating in the Saving and Empowering Young Lives in Europe (SEYLE) school-based multicenter control sample. Multilevel Structural Equation Models were used, controlling for sociodemographic variables. Victimization was considered chronic when a student was victimized in the first two time points and sporadic when it was reported only at one point but not in another. Results Bidirectional prospective association between all types of victimization and depression were found. Among participants, who reported victimization once (but not twice), physical victimization, but not verbal and relational, was associated with later suicidal ideation and attempts. Chronic victimization of any type increased likelihood for later depression compared with sporadic and no-victimization. Chronic relational victimization increased the likelihood of later suicidal ideation, and chronic physical victimization increased the likelihood for suicidal attempts. Conclusions The results support the bidirectional effect of victimization and depression and indicate that there are complex longitudinal associations between victimization and suicidal ideation/attempts. Physical victimization may especially carry effect on suicidal risk over time. Interventions should focus on victimization as a cause of distress but also aim to prevent vulnerable adolescents from becoming targets of victimization.
First published online: 19 July 2018
Gesehen am 02.04.2019